Ab initio description of disorder effects in layered cathode active materials by the coherent potential approximation - Eckhardt, Janis K; Risius, Philipp E; Czerner, Michael; Heiliger, Christian; Justus Liebig University Giessen (My University, 2022)
Disorder effects in alloys are usually modeled by averaging various supercell calculations considering different positions of the alloy atoms. This approach, however, is only possible as long as the portion of the individual components of the alloy is sufficiently large. Herein, we present an ab initio study considering the lithium insertion material Li1−x[Ni0.33Co0.33Mn0.33]O2 as model system to demonstrate the power of the coherent potential approximation within the Korringa–Kohn–Rostoker Green's function method. This approach enables the description of disorder effects within alloy systems of any composition. It is applied in this study to describe the (de-)intercalation of arbitrary amounts of lithium from the cathode active material. Moreover, we highlight that using either fully optimized structures or experimental lattice parameters and atomic positions both lead to comparable results. Our findings suggest that this approach is also suitable for modeling the electronic structure of state-of-the-art materials such as high-nickel alloys.
Keywords: density functional theory (DFT); Korringa–Kohn–Rostoker (KKR) method; coherent potential approximation (CPA); lithium-ion battery; disorder effects; cathode active material (CAM); NCM; ddc:530